MANTRA PENGASIH MANDI ULAR CINTAMANI: KAJIAN STRUKTURAL, FUNGSI, DAN IMPLEMENTASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Syarifah, Siti; Syifanaya, Raissa; Fahira, Dima Azharul; Mulyaningsih, Indrya (ppjbsip, 2023)
Abstract: This study aims to describe or describe the structure, function, and meaning of the self-compassion mantra, namely the mantra